Environmental Impact of Agrochemical uses on the Island's Agricultural Production Area in Maranhão, Brazil (Global Journal of Science Frontier Research, 2020)
Agriculture is the foundation of society, has provided humanity with its food needs for over ten thousand years. The use of pesticides in Brazil and the world has grown exponentially in recent decades. The objective of this study was assessment the use of agrochemicals and their environmental impact on agricultural production of the Island of Maranhão. The study area is located in Paço do Lumiar, Maranhão, Brazil. Soil samples were collected from agricultural land during the wet season (between the months of February and May) and dry season (between the months of September and October) seasons of 2018.
Keywords: agriculture; soil; pesticides; adsorption.